Penatalaksanaan fisioterapi pada kasusBell's palsy dextra di RST. Dr. Soedjono magelang - Putri, Erwin Prasiwi Utami; , Maskun Pudjianto, S.MPH., M.Kes (2016)
Background: Bell's palsy is a condition by facialis nerve attact which serves face muscle.These conditions result in paralysis on one side of the face such as forehead can't contricting,raised eyebrow, close eye with perfect at lesions side, inflate deflate nose, asymmetric smiling, asymmetric pout, gargle leak and face attracted towards healthy with marked lopsided mouth.the cause of bells palsy until now not known with certainty or idiopathic but no mention of the cause of bells palsy id a conditious wind exposure or due to virus infection resulting in dagame to the nerves. Objective: to investigate the benefit of using modalities such as infrared, electrical stimulation, mirror exercise for blood circulation in face area, increasing muscle strength and functional activity of face by bell's palsy condition.. Result: measurement muscle strength using Manual Muscle Testing (MMT) for m.frontalis, m.corrugatorsupercili, m.orbicularis oculi, m.nasalis, m.depresoranguli, and m.mentalis from T1-T6 find out result increasing from 0 becomes 1, m.orbicularis oculi from T1-T6 increasing become 3, m.zigomaticum from T1-T6 incresing at T6 become 3, m.bucinator T1-T6 increasing at T6 become 3. Functional activity of faces functional activity assessed by ugo fisch scale from T1-T6 find out result from 20 increasing become 42. Conclusion:using modalities such as infrared, electrical stimulation, mirror exercise can increasing strength muscle and faces functional activity from Bell's palsy conditions.